2001
DOI: 10.1006/jabr.2000.8726
|View full text |Cite
|
Sign up to set email alerts
|

Double Centralizer Properties, Dominant Dimension, and Tilting Modules

Abstract: Double centralizer properties play a central role in many parts of algebraic Lie theory. Soergel's double centralizer theorem relates the principal block of the Bernstein ᎐Gelfand᎐Gelfand category O O of a semisimple complex Lie algebra with Ž the coinvariant algebra i.e., the cohomology algebra of the corresponding flag . manifold . Schur᎐Weyl duality relates the representation theories of general linear Ž . and symmetric groups in defining characteristic, or via the quantized version in nondefining character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 12 publications
0
64
0
Order By: Relevance
“…By Theorem 4.8 and Corollaries 4.9 and 4.6, P c ⊗ V ⊗d is a direct sum of all the self-dual projective indecomposable modules in O d c (λ), each appearing with some non-zero multiplicity. Applying [KSX,Theorem 2.10] as in the proof of [KSX,Theorem 3.2], the proof of the first statement reduces to checking that there exists an exact sequence 0 → P 0 → P 1 → P 2 in O d c (λ) such that P 0 is a projective generator and P 1 , P 2 are self-dual projectives. To see this, there is for…”
Section: )-Mod Is Fully Faithful On Projective Modules In Particularmentioning
confidence: 99%
See 1 more Smart Citation
“…By Theorem 4.8 and Corollaries 4.9 and 4.6, P c ⊗ V ⊗d is a direct sum of all the self-dual projective indecomposable modules in O d c (λ), each appearing with some non-zero multiplicity. Applying [KSX,Theorem 2.10] as in the proof of [KSX,Theorem 3.2], the proof of the first statement reduces to checking that there exists an exact sequence 0 → P 0 → P 1 → P 2 in O d c (λ) such that P 0 is a projective generator and P 1 , P 2 are self-dual projectives. To see this, there is for…”
Section: )-Mod Is Fully Faithful On Projective Modules In Particularmentioning
confidence: 99%
“…Theorem B should be compared with Soergel's Endomorphismensatz from [S]; the connection with Whittaker modules in that case is due to Backelin [Ba]. As observed originally by Stroppel [S1, Theorem 10.1] (as an application of [KSX,Theorem 2.10]), there is also a version of Soergel's Struktursatz for our parabolic setup: the functor Hom g (P ⊗ V ⊗d , ?) is fully faithful on projective objects.…”
Section: Introductionmentioning
confidence: 95%
“…Then by classical results of Morita, Tachikawa and others (see [30]) there is a double centralizer property between A and its centralizer subalgebra eAe: End A (Ae) = eAe and End eAe (Ae) = A. In [19] it has been shown that classical Schur-Weyl duality between the Schur algebra S(n, r) (for n ≥ r) and the group algebra kΣ r of the symmetric group as well as Soergel's 'Struktursatz' for the Bernstein-Gelfand-Gelfand category O, providing a double centralizer property between a block and a subalgebra of the coinvariant algebra, both are special cases of this situation. In particular, those Schur algebras and also blocks of O have dominant dimension at least two.…”
Section: Preliminariesmentioning
confidence: 99%
“…As examples, (quantized) Schur algebras S q (n, r) with n ≥ r and block algebras of Bernstein-Gelfand-Gelfand category O are in A ; see [13,15,19]. Indeed, each such algebra has a set of idempotents fixed by the involution defining the duality and generating the ideals in a heredity chain.…”
Section: Characterizations and Comparisons Of Dominant Dimensionmentioning
confidence: 99%
See 1 more Smart Citation